Effect of Stirring Speed and Stirring Time on Distribution of Nano Al2O3 Particles in Al7075 Metal Matrix Composite - Raju, H. P.; Prashanth Reddy, M. S. (Asian Journal of Engineering and Applied Technology, 2019)
Al7075 was successfully synthesized with the addition of Nano Al2O3 with 1.00Wt% by stir casting method by considering various stirring speeds and stirring times during this study. Scanning Electron Microscopy (SEM) is adapted to examine the microstructure of prepared composites. Tensile strength are tested on composite specimens (as per ASTM E8M-09) using computerized Universal Testing Machine (UTM). Micro Vicker’s hardness test was carried out on top of the polished composite specimens. The results showed the microstructure, ultimate tensile strength and hardness of the composite were influenced by the stirring speed and stirring time. From the microstructure it is revealed that, the particle clustering was more at a lower stirring speed with a lower stirring time. Increased mixing speed and mixing time resulted in better particle distribution. The results of the hardness test also demonstrated that, the composite’s hardness is affected by the stirring speed and time. At 400 rpm with a stirring time of 10 minutes, the uniform hardness levels are achieved. But the properties degraded again after an interval of certain time. Present study is conducted to determine microstructure, ultimate tensile strength, and hardness of composite and the tendency between processing parameters such as stirring speed and time.